Is the second wave of COVID-19 socially retrogressive? Social liaison is the need of hour - Govil, Gaurav; Tomar, Lavindra; Dhawan, Pawan (International Journal Of Community Medicine And Public Health, 2021)
The challenges of COVID-19 pandemic have invoked changes in behavioral patterns of the society. The retrogressive behavior has been one of the most frequently exhibited changes in behavior. There has been both a physical and emotional imbalance for the society at large. There has been an utter lack of empathy for the practiced cultural values and civilization norms.